Indonesian Islam in Religious and Political Struggle Discourse - Taufani Taufani (Al-Albab, 2015)
This paper looks into the struggle between Islam and politics in Indonesia from Soekarno-era up to the Reform. So far, Islam in Indonesia has been known as unique because of its history. When Islam entered Indonesia, it was mystical in nature, accommodating towards local religion and culture that existed before its arrival. In the wake of the emergence of the nation-State concept in this modern age, the struggle between Islam and politics in Indonesia tends to be characterized by the presence dialectic that continues to take place, i.e. whether Islam should adopted as the sole ideology and the state positive law of the country or on the contrary where it should become the ethics and values in the spirit of the nation and State. This indicates that the struggle between Islam and politics in Indonesia is not static, but rather it tends to be dynamic and volatile as it is strongly affected by changes in the political landscape in each era of Government.